2019
DOI: 10.3390/jcm8010087
|View full text |Cite
|
Sign up to set email alerts
|

Altered Adipose Tissue DNA Methylation Status in Metabolic Syndrome: Relationships Between Global DNA Methylation and Specific Methylation at Adipogenic, Lipid Metabolism and Inflammatory Candidate Genes and Metabolic Variables

Abstract: Metabolic syndrome (MetS) has been postulated to increase the risk for type 2 diabetes, cardiovascular disease and cancer. Adipose tissue (AT) plays an important role in metabolic homeostasis, and AT dysfunction has an active role in metabolic diseases. MetS is closely related to lifestyle and environmental factors. Epigenetics has emerged as an interesting landscape to evaluate the possible interconnection between AT and metabolic disease, since it can be modulated by environmental factors and metabolic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 71 publications
(78 reference statements)
4
57
0
2
Order By: Relevance
“…Deletion of SCD1 gene product in mice could effectively improve insulin sensitivity, reduce plasma non-HDL-cholesterol and triglyceride levels and liver lipid accumulation as well as increase bene cial HDL-cholesterol levels [49]. Daniel Castellano-Castillo et al also found that a negative relationship between SCD DNA methylation and BMI and the MetS index [50]. In the current study, we also noticed that SCD was mainly involved in fatty acid metabolism and biosynthesis of unsaturated fatty acids pathways.…”
Section: Discussionsupporting
confidence: 68%
“…Deletion of SCD1 gene product in mice could effectively improve insulin sensitivity, reduce plasma non-HDL-cholesterol and triglyceride levels and liver lipid accumulation as well as increase bene cial HDL-cholesterol levels [49]. Daniel Castellano-Castillo et al also found that a negative relationship between SCD DNA methylation and BMI and the MetS index [50]. In the current study, we also noticed that SCD was mainly involved in fatty acid metabolism and biosynthesis of unsaturated fatty acids pathways.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, limitations and critical aspects of the interpretation should be discussed one of which is that the analyses were on whole tissue samples instead of isolated adipocytes, as in other comparable studies [13,19,36,43] and due to the initially limited sample material available, protein expression analysis could not be performed here. It has been reported that in non-obese humans, macrophages can represent 10-25% of the immune cellular population in VAT, while in an obese condition this range is increased to 40-50% [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have described a direct relationship between visceral 2 of 13 adipose tissue (VAT) and the development of the pre-diabetic condition and diabetes. Mechanistically, this has been critically related to the inflammatory processes within adipose tissue, especially in visceral [13,14]. The particular pathophysiological role and precise mechanisms/factors within VAT for GDM are increasingly of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral adipose tissue is a metabolically active endocrine organ that has been linked to the development of obesity and obesity-related comorbidities (23, 24). Understanding the epigenetic and molecular differences in VAT of adolescents with obesity in comparison to lean counterparts may help identify potential therapeutic targets and further inform our understanding of tissue dysfunction in obesity.…”
Section: Discussionmentioning
confidence: 99%